Phytochemistry, metabolism, and ethnomedical scenario of honey: A concurrent review. (18th December 2017) - Ahmad, Rabia Shabir; Hussain, Muhammad Bilal; Saeed, Farhan; Waheed, Marwa; Tufail, Tabussam
ABSTRACT: Honey is a natural domestic sweet food material and a chemically diverse superfluous product of nectar acquired from flowers. Owing to the presence of higher amounts of antioxidant compounds covering phenolic, enzymes, organic acids, and bioactive peptides, it holds a strong ability to prevent various maladies. In addition, honey has also been exploited in certain cardiovascular, gastrointestinal, neoplastic, and inflammatory states along with its role in the treatment of copious infections and surgical wounds. Flavonoids and polyphenols are important bioactive components present in honey and have antioxidant properties. Some bioactive compounds, for example luteolin, galangin, isorhamnetin, quercetin, and kaempferol, are present in honey. Phenolic acids and flavonoids have important pharmacological activities such as anti-allergic, anti-biotic, anti-carcinogenic, and hypoglycaemic. Moreover, curative potential of bioactive components and their utilisation in value added food products are also the limelight of this article.